Magnetic resonance imaging of the liver and spleen in the diagnosis of storage diseases - Z. M. Shapieva; O. V. Kucheruk; V. E. Sinitsyn; E. A. Mershina (Вестник рентгенологии и радиологии, 2016)
Storage diseases (thesaurismoses, storage reticuloses) are the common name of a large group of hyperplastic non-leukemic diseases characterized by congenital or acquired metabolic disturbances and abnormal accumulation of metabolic products in blood and/or cells of different organs and by hyperplasia of mononuclear phagocyte elements in the liver, spleen, bone marrow, lymph nodes, and other organs, which makes the diseases systemic. Among the imaging techniques for diffuse liver diseases, ultrasonography and X-ray computed tomography are most commonly used for their diagnosis and follow-up. Magnetic resonance imaging (MRI) has the highest sensitivity and specificity in diagnosing liver diseases. The paper considers the current MRI procedures that are used to diagnose storage diseases and to quantify found changes. For Gaucher’s disease, the potentials of novel techniques, such as MR spectroscopy, diffusion-weighted imaging (DWI), and chemical shift imaging (Dickson’s method) for the estimation of revealed changes, are described. For hemochromatosis, the contribution of T2 WI to the quantification of iron overload in the liver parenchyma is depicted, which is an alternative invasive procedure in its determination. Incorporation of MRI into the examination algorithm for patients with storagediseases will be able to improve the detection of these rare diseases and to monitorthe efficiency of performed therapy.